PENGARUH PERSEPSI HARGA DAN INOVASI PRODUK TERHADAP MINAT PEMBELIAN (STUDI PADA UMKM NCASA STONE CURVING GIANYAR) - Ni Putu Iin Budi Purnama; Ni Kadek Meilda Dwiarta Sari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Purchase intention is one of the psychological aspects that has a considerable influence on behavioral attitudes. A person's buying interest is influenced by price perceptions and product innovations they have. The purpose of this study was to examine and obtain empirical evidence of the effect of price perception and product innovation on the purchase intention of stone carving reliefs at Ncasa Stone Curving Gianyar. The object of this research is the influence of price perception and product innovation on buying interest in the relief carving products of padas stone at Ncasa Stone Curving Gianyar. The population used in this research is people who have visited and seen Ncasa Stone Curving carving products whose population is not known for sure. The sampling method using the non-probability sampling method is sampling which does not provide equal opportunities or opportunities for each member of the population to be selected as a sample. So that the technique of determining the sample is done by purposive sampling, namely the technique of determining the sample based on certain criteria or considerations. The result of this study is that price perception has a positive and significant effect on buying interest at NCasa Stone Curving Gianyar. This means that the better consumer price perceptions of NCasa Stone Curving Gianyar will increase the interest in buying the product. Product innovation has a positive and significant effect on buying interest at NCasa Stone Curving Gianyar. This means that the better product innovations owned by NCasa Stone Curving Gianyar will increase the interest in buying products.